2022
DOI: 10.1186/s12885-022-09275-z
|View full text |Cite
|
Sign up to set email alerts
|

The PI3K/AKT/mTOR signaling pathway is aberrantly activated in primary central nervous system lymphoma and correlated with a poor prognosis

Abstract: Background Primary central nervous system lymphoma (PCNSL) is a specific subtype of non-Hodgkin lymphoma that is highly invasive and confined to the central nervous system (CNS). The vast majority of PCNSLs are diffuse large B-cell lymphomas (DLBCLs). PCNSL is a highly heterogeneous disease, and its pathogenesis has not yet been fully elucidated. Further studies are needed to guide individualized therapy and improve the prognosis. Methods In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The phosphatidylinositol 3-kinase (PI3K) pathway is one of the most important signaling networks in cancer ( 14 , 21 , 22 ), and plays an important role in the regulation of cell growth, proliferation, migration, survival, and glucose metabolism ( 23 , 24 ). The expression of AKT1 and mTOR, as downstream proteins of the PI3K signaling pathway, reflects the status of the pathway, while their decreased expression reflects its inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…The phosphatidylinositol 3-kinase (PI3K) pathway is one of the most important signaling networks in cancer ( 14 , 21 , 22 ), and plays an important role in the regulation of cell growth, proliferation, migration, survival, and glucose metabolism ( 23 , 24 ). The expression of AKT1 and mTOR, as downstream proteins of the PI3K signaling pathway, reflects the status of the pathway, while their decreased expression reflects its inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…(2022) reported that the PI3K–AKT–mTOR pathway was aberrantly activated in primary central nervous system lymphoma (PCNSL) and was associated with a poor prognosis. In addition, phosphorylated AKT was found to be widely expressed in 65.1% of patients with PCNSL [ 72 ]. At the same time, George et al.…”
Section: Pi3k/akt/mtor Signalling Pathwaymentioning
confidence: 99%
“…Since the PI3K/AKT/mTOR pathway is aberrantly active in DLBCL and plays a role in the genesis and progression of DLBCL [ 365 369 ], researchers have also investigated its role in PCNSL. Zhang et al found that the recurrence rate of PCNSL in the phospho-mTOR-positive group was 64.5%, which was substantially greater than in the negative group.…”
Section: Prognostic Markers For Pcnslmentioning
confidence: 99%